2022
DOI: 10.3390/antibiotics11111474
|View full text |Cite
|
Sign up to set email alerts
|

The Antimicrobial Peptide AMP-17 Derived from Musca domestica Inhibits Biofilm Formation and Eradicates Mature Biofilm in Candida albicans

Abstract: The biofilm formation of C. albicans represents a major virulence factor during candidiasis. Biofilm-mediated drug resistance has necessitated the search for a new antifungal treatment strategy. In our previous study, a novel antimicrobial peptide named AMP-17 derived from Musca domestica was confirmed to have significant antifungal activity and suppress hyphal growth greatly in C. albicans. In the current work, we aimed to investigate the antibiofilm property of AMP-17 in C. albicans and explore the underlyin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…These results can be taken with a sufficient optimism regarding the potential of AMP/antiseptic implementation in coatings of medical devices, routine care products, or acute wound treatment. At the same time, literature data [ 22 , 125 , 126 ] suggest that eradicating well-established biofilms can require an order of magnitude higher concentrations of AMPs than the ones needed for the prophylactic against their formation or require prolonged exposure [ 127 ]. Thus, to properly assess the prospects of combined use of AMPs and antiseptics against such challenges, additional testing on preformed biofilms will be important.…”
Section: Resultsmentioning
confidence: 99%
“…These results can be taken with a sufficient optimism regarding the potential of AMP/antiseptic implementation in coatings of medical devices, routine care products, or acute wound treatment. At the same time, literature data [ 22 , 125 , 126 ] suggest that eradicating well-established biofilms can require an order of magnitude higher concentrations of AMPs than the ones needed for the prophylactic against their formation or require prolonged exposure [ 127 ]. Thus, to properly assess the prospects of combined use of AMPs and antiseptics against such challenges, additional testing on preformed biofilms will be important.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, it has been demonstrated that cell surface hydrophobicity is altered by filamentation in Candida tropicalis (50). Several drugs have also been reported to reduce cell surface hydrophobicity and inhibit filamentous growth in C. albicans (51)(52)(53)(54)(55)(56)(57)(58)(59)(60). Therefore, it is possible that there exist mechanisms that simultaneously regulate cell surface hydrophobicity and cell morphology in dimorphic yeasts and that Mar1 is involved in their regulation in Y.…”
Section: Discussionmentioning
confidence: 99%
“…The action of other AMP classes to control C. albicans biofilm has been observed in the literature. AMP-17 peptide showed strong efficacy in C. albicans (SC 5314), inhibiting 86% of mature biofilm [ 43 ]. Additionally, the gH625-M membranotropic peptide showed efficacy, inhibiting 52% of persistently derived C. albicans (ATCC 90028) by targeting the structure of the cell membrane [ 44 ].…”
Section: Discussionmentioning
confidence: 99%